Penerapan Pendekatan Teaching At The Right Level (TARL) Untuk Meningkatkan Motivasi Dan Pemahaman Konsep Bilangan Berpangkat Di Kelas VIII - Lania, Renna; Soraya, Ratna; Nasution, Cholizah (LPPM Universitas PGRI Argopuro Jember, 2024)
This study is motivated by the low motivation and conceptual understanding among the eighth-grade students at UPT SMP Negeri 8 Medan. The existing teaching methods, which do not address the students' needs or sufficiently motivate them, have led to a poor grasp of mathematical concepts, particularly in exponentiation. The